PENINGKATAN KUANTITAS PRODUKSI DAN KUALITAS DESAIN BATIK SERTA PENAMBAHAN PERALATAN DI PERUSAHAAN BATIK KARTIKA TIRTOMOYO WONOGIRI - KURNIADI, EDI; Sumartono, Basuki; Wahida , Adam (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
The service partner is Mr. Aris Supriyadi's Batik Kartika Business, located in Bugel Hamlet, Tirtomoyo Village, Tirtomoyo District, Wonogiri Regency, which is facing the main problems of: 1) Low product innovation due to the lack of maximum development of batik designs that can contribute to competitiveness among similar products, 2) Lack of complete equipment that supports increasing the quantity and quality of production. The implementation of this activity program, using a mentoring and training approach; In this context, the training in question is to provide some knowledge of the batik production process, the development of designs that have local distinctiveness for seven tourist attractions, and transfer of experience in exhibiting regional superior products, especially batik as a promotional event and marketing improvement. The results of the activity are an increase in knowledge about design as one of the determinants of product competitiveness, and crafters have improved skills in making designs with local potential sources of ideas. Partners have been given additional equipment in the form of stoves for stamped batik, stamp tables, and equipment for boiling/removing wax in the form of kenceng. Improved marketing through assistance in the Wonogiren Batik Festival to commemorate the 82nd Anniversary of Wonogiri Square.